Improving access to adult vaccination: a tool for healthy ageing. Issue 2 (3rd June 2014) - Scrutton, Jonathan; Sinclair, David; Walker, Trinley
Abstract : Purpose: – The purpose of this paper is to demonstrate how access to vaccination for older people in the UK can be both improved and used as a tool for healthy ageing. Design/methodology/approach: – ILC-UK released a report "Adult Immunisation in the UK", which applied a UK perspective to a 2013 Supporting Active Ageing Through Immunisation (SAATI) report on immunisation. The ILC report combined the SAATI findings with a traditional literature review, a policy review incorporating grey literature and the outcomes of a focus group discussion. This paper highlights the key findings of the ILC-UK report. Findings: – Vaccination needs to be included as part of proactive strategies to promote healthy and active ageing. Initiatives need to be explored that increase the rate of delivery of vaccinations. Barriers to the vaccination of health and social care professionals working with older people need to be removed. The government should explore using psychological insights into human behaviour to improve the take-up of vaccinations amongst adults. The range of settings where older people can receive vaccination needs to be expanded. Information on the potential benefits of immunisation should be made readily available and easily accessible to older people. Practical implications: – The paper calls for a structural shift in how vaccination services in the UK are organised. Social implications: – The paper calls for a cultural shift in how society views immunisation and the role it has to play in the healthy ageing process. Originality/value: – The paper uses new European research on immunisation and applies it to the UK's situation.